2010
DOI: 10.1152/jn.00141.2010
|View full text |Cite
|
Sign up to set email alerts
|

Functional Networks in the Anesthetized Rat Brain Revealed by Independent Component Analysis of Resting-State fMRI

Abstract: Hutchison RM, Mirsattari SM, Jones CK, Gati JS, Leung LS. Functional networks in the anesthetized rat brain revealed by independent component analysis of resting-state fMRI. J Neurophysiol 103: 3398-3406, 2010. First published April 21, 2010 doi:10.1152/jn.00141.2010. The rodent brain is organized into functional networks that can be studied through examination of synchronized low-frequency spontaneous fluctuations (LFFs) of the functional magnetic resonance imaging -blood-oxygen-level-dependent (BOLD) signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
144
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(179 citation statements)
references
References 56 publications
29
144
5
1
Order By: Relevance
“…fmrib.ox.ac.uk/fsl), to extract a group-averaged functional network that included the bilateral sensorimotor cortex. This data-driven approach allows unbiased identification of whole functional networks from included animals, without the need to coregister to an extrinsic rat brain atlas to select diverse brain regions that are assumed to be part of a larger functional network (Hutchison et al, 2010;Jonckers et al, 2011). We found that analysis with seven components yielded a component of which the anatomical pattern most ideally matched with the bilateral sensorimotor cortices (see Fig.…”
Section: Methodsmentioning
confidence: 96%
“…fmrib.ox.ac.uk/fsl), to extract a group-averaged functional network that included the bilateral sensorimotor cortex. This data-driven approach allows unbiased identification of whole functional networks from included animals, without the need to coregister to an extrinsic rat brain atlas to select diverse brain regions that are assumed to be part of a larger functional network (Hutchison et al, 2010;Jonckers et al, 2011). We found that analysis with seven components yielded a component of which the anatomical pattern most ideally matched with the bilateral sensorimotor cortices (see Fig.…”
Section: Methodsmentioning
confidence: 96%
“…OFI provides uniquely high spatial resolution (e.g., ∼6 μm for λ 1 -λ 3 channels, ∼30 μm for λ 4 channel or LSI, and ∼10 μm for ODT) and large FOV (e.g., 5 × 6 mm 2 ), which allows the simultaneous study of hemodynamic, metabolic, and cellular characteristics in various vascular compartments [e.g., arteriolar flow (AF) and venular flow (VF)] and in brain tissue.. For brain functional studies in rats (e.g., LFOs), two major sources of artifacts include heartbeats at f sys ∼4-4.5 Hz (may vary slightly from animal to animal and with its physiological conditions) and respiration rate at f res = 1 Hz (incubated, controllable). According to the Nyquist sampling theorem, a sampling rate of f s /2 ≥ max{f sys , f res }, i.e., f s >9 Hz, is needed to eliminate the aliasing artifacts resulting from the folding back of f sys and f res components to the LFOs in the low-frequency range (53)(54)(55)(56)(57). Because LSI is a full-field acquisition modality, simultaneous images in CBFv, HbO 2 , and HbR from cerebrovascular vessels and cortical tissue (including capillaries and vessels <ϕ30 μm) along with Ca 2+ i fluorescence fluctuations in the resting state can be acquired with OFI at ∼30 μm/16 Hz spatiotemporal resolutions and over FOV of 5 × 6 mm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a rat exposed to hypercapnia, brain activations were higher in conscious animals than those anaesthesia with isoflurane (Sicard et al 2003). Conversely, the networks of vision, motor or auditory sensitivity described in the resting state persisted regardless of the depth or type of general anaesthesia (Hutchison et al 2010), and no difference between anaesthetics was found after visual stimulation in dogs (Willis et al 2001). Several MRI paradigms in anaesthetized animals have been developed to map brain activation induced by serotonin infusion in the baboon (Wey et al 2010) and cat (Henderson et al 2002) or brain connectivity in the rat (Pawela et al 2009, Zhao et al 2008).…”
Section: Pratical Issues Anaesthesia and Immobilization Of Animalsmentioning
confidence: 99%
“…In other words, ICA identifies functionally connected brain networks which covary independently of other regions. ICA has been used to explore resting state and functional connectivity in arousal states in humans, non-human primates (Moeller et al 2009) and rodents (Hutchison et al 2010). …”
Section: Other Experimental Paradigmsmentioning
confidence: 99%